Language Fashion in Online Media: Observations on Some Communication Practices - Ivanova, Iva (Media and Language, 2021)
The article analyzes the concept of language fashion as a linguocultural, sociolinguistic and linguistic phenomenon that influences the style of modern media and in particular online media. It is pointed out how some specifics of online media such as the possibility for regular updating of information, hypertextuality, multimedia presentation of information and active participation of users in creating the information flow reflect on the emergence and imposition of fashionable language patterns. Language fashion is seen as a means of manipulating information in the online environment. The summary is made that despite some specifics in the creation and assimilation of fashionable language patterns (rapid assimilation of language models; unsustainability of some language innovations; entry of language patterns from social networks; search for a balance between expression and standard), online media follow common to most media language models.
Keywords: language fashion; online media; language models; connotative stylistics; figures and tropes